An investigation into the effects of smoke-water and GR24 on the growth of nicotiana benthamiana seedlings - Kotze, Liske Marinate (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Plant Biotechnology))--University of Stellenboscg, 2010.